Exosomal microRNAs induce tumor-associated macrophages via PPARγ during tumor progression in SHH medulloblastoma - Zhu, Liangyi; Yang, Ying; Li, Haishuang; Xu, Luzheng; You, Huanyu; Liu, Yantao; Liu, Zongran; Liu, Xiaodan; Zheng, Danfeng; Bie, Juntao; Li, Jiaqi; Song, Chao; et al. (Cancer letters, 2022)
Medulloblastoma (MB), the most common malignant pediatric brain tumor, is composed of at least four molecular subgroups with distinct clinical characteristics. The sonic hedgehog (SHH) subgroup exhibits the most abundant tumor-associated microglia/macrophages (TAMs) infiltration. SHH-MB patients treated by anti-SHH drugs showed high drug resistance. However, the comprehensive role of TAMs in SHH-MB remains enigma. The aim of this study is to explore the mechanism of TAM activation/polarization in SHH-MB and discover a potential immunotherapeutic target to reduce drug resistance. We first analyzed expression profiles of immuno-microenvironment (IME) in four subgroups of 48 MB tumors using NanoString PanCancer IO360 panel and found TAMs were the major component of IME in SHH-MBs. We further distinguished M1/M2-like TAMs in tumors and found M2-like macrophages, rather than microglia, were enriched in SHH-MBs. In transgenic SHH-MB mice, these TAMs had close relationship with tumor progression. Polarization of the TAMs could be induced by MB-derived exosomes in vitro. We then screened SHH MB-derived exosomal miRNAs and their target genes using RNA sequencing and luciferase assay to clarify their roles in regulating TAM polarization. We found down-regulated let-7i-5p and miR-221-3p can induce M2-like polarization of TAMs via upregulating peroxisome proliferator activated receptor gamma (PPARγ). Finally, we demonstrated the PPARγ antagonist efficiently improved the antitumor activity of SMO inhibitor in vivo, which may be related to inhibition of M2-like TAMs. Our findings suggest a potential therapeutic strategy for SHH-MB by targeting tumor-supportive M2-like TAMs to enhance the therapeutic effect of SMO inhibitors. •Increased M2-like TAM infiltration is associated with SHH-MB progression in vivo.•M2-like macrophages, rather than microglia, were enriched in SHH-MBs.•SHH MB-derived exosomal miRNAs can induce M2-like polarization of TAMs via PPARγ.•PPARγ antagonist efficiently improved the antitumor activity of SMO inhibitor in vivo.